2010
DOI: 10.1007/s11250-010-9582-6
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of risk of gastrointestinal parasitic infection in cattle in North Eastern States of India

Abstract: Gastrointestinal parasitic infection is highly prevalent in the North Eastern States (NEH) of India and accounted for significant economic losses across various livestock species. Productivity of cattle in terms of milk yield was estimated to be considerably higher (3,715, 3,590, and 3,154 L) due to strategic anthelmintic treatment as compare to control group (2,928 L). Based on the probability of occurrence of parasitic infection as well as increase in value of milk production, the possible economic gain at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Gastrointestinal parasitic diseases are the major cause of economic losses in domestic animals worldwide (Corwin, 1997;McLeod, 1995;Grisi et al, 2014;Bandyopadhyay et al, 2010). Decreased inappentence lead to problems of feed and water intake, whilst protein losses due to gastrointestinal damage diminishes availabilities for growth.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal parasitic diseases are the major cause of economic losses in domestic animals worldwide (Corwin, 1997;McLeod, 1995;Grisi et al, 2014;Bandyopadhyay et al, 2010). Decreased inappentence lead to problems of feed and water intake, whilst protein losses due to gastrointestinal damage diminishes availabilities for growth.…”
Section: Introductionmentioning
confidence: 99%
“…The worms were individually identified, on the basis of copulatory bursa and spicules, by light microscopy [5] and the keys provided by Whitlock (1960) [22]. The DNA was extracted, as described by Sambrook and Russell (2001) [23], with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Occurrence of M. digitatus was recorded as early as the 1920s, from the abomasum of cattle in India [3], [4]. Various studies have confirmed the presence of M. digitatus infection in cattle and buffaloes in different parts of India [5], [6], [7], [8]. M. digitatus may be found in mixed infection in ruminants along with other GINs such as Ostertagia ostertagi , Trichostrongylus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The adult paramphistomes are the major parasites of rumen and reticulum of ruminants, which cause localized loss of rumen papillae, responsible for ruminitis, irregular rumination, unthriftness, lower feed conversion and loss of body condition. Various reports on paramphistomosis from different states representing different geographical locations of the country are available (Samanta and Santra, 2009;Bandyopadhyay 2010;Kumari et al, 2010;Swarnkar et al, 2010;Yadav et al, 2010;Khajuria et al, 2011;Rahman et al, 2012;Maitra et al, 2014). A study on prevalence limited only to cattle amphistomosis has also been conducted from Andhra Pradesh by Kumari and Hafeez, (2005).…”
Section: Introductionmentioning
confidence: 99%